IMMEDIATE AND LONG-TERM RESULTS OF THE LEFT ATRIUM AURICLE OCCLUDER IMPLANTING IN ATRIAL FIBRILLATION - Z. Kh. Shugushev; L. V. Rodionova; О. N. Ganeeva; N. V. Morozova; D. A. Maksimkin (Российский кардиологический журнал)
Aim. To evaluate the safety and efficacy of the “WATCHMAN” occluder (OW) in atrial fibrillation patients (AF) during hospital period and in 12 months after the procedure.Material and methods. Frоm 2013 to 2015 years, in the N. A. Semashko Central clinical hospital № 2 of “RZD”, 15 OW were implanted to patients with persistent AF of non-rheumatic origin, admitted for electro cardioversion, or electrophysiological study and radiofrequency ablation, pacemaker implantation. Indications for endovascular intervention were the threat of repeated embolism, high bleeding risk, severe comorbidities, and inefficacy of antithrombotic therapy. From the study were excluded those with stenosis of the left atrioventricular space and thrombi in the left atrium auricle (LAA). During pre-surgery period, all patients underwent standard transthoracal and transesophageal echocardiography for assessment of the LAA anatomy, its size in four points of view and its position to the left upper pulmonary vein. For stroke risk assessment and of thromboemolic complications the score CHA2 DS2 was used and its new edition CHA2 DS2 -VASc. Before the discharge from clinic, all patients underwent transesophageal echocardiography, repeated in 6 weeks, 6 and 12 months.Results. Mean age of patients was 52 year old. All patients had successful OW implanting. Interventions were done without general anesthesia, under local anesthesia. Mean duration of surgery was 42±11,3 min. To every patient one device was utilized. There were no replacements of OW for wrong sizing or other reasons. In 5 patients (anatomy as “chicken wing”) under angles 90-135º there was protrusion of lower border of OW found by 1/3 of the length. In patients with LAA OW sizes 33 and 27, there was residual flow registered under the lower border, of5 mmand2 mmdiameter, respectively. There were no complications during operation and nearest post-operation period. In 12 months after the study there was not dislocation, embolization or position changes among the devices. The residual flow diameter in33 mmimplant patient decreased in 6 months from 5 to2 mm, in the other — remained2 mm. No patients had brain circulation disorders and other embolies.Conclusion. The method of OW implanting into LA of non-rheumatic origin is effective method of embolic complications prevention, not followed by bleedings and making to prognosis improvement of this kind of patients, as to quit entire life anticoagulation